أسس وتطبيقات منهج الرسول الكريم عليه الصلوة والسلام في تربية البنات في مرحلة الطفولة وما قبلها: The Methods & Applications of the Prophetic Approach regarding raising girls in childhood and before. - Dr. Haris Saleem; Dr. Kafait Ullah Hamdani (Seerat Studies, 2023)
Islam is a religion of mercy to all people, both male and female as they are the two main pillars of human society. A woman can play a vital role in a society if only she is brought up with care, love and justice. Islam balanced mankind by addressing the issue of a female in a society and showed her duties and role in a society. This research is aimed to identify the fundamentals of the prophetic practice and guidance regarding upbringing girls in childhood and before. The article proceeds with an introduction, importance of training daughters and some fundamental principles regarding raising girls. The article applies descriptive and applied method for the research. Various findings and recommendations are presented very precisely in the conclusion .